2021
DOI: 10.1007/978-3-030-78292-4_38
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Students’ Experiences with Collaboration Analytics for Remote Group Meetings

Abstract: Remote meetings have become the norm for most students learning synchronously at a distance during the ongoing coronavirus pandemic. This has motivated the use of artificial intelligence in education (AIED) solutions to support the teaching and learning practice in these settings. However, the use of such solutions requires new research particularly with regards to the human factors that ultimately shape the future design and implementations. In this paper, we build on the emerging literature on human-centred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
1
4
1
Order By: Relevance
“…As Bourdieu ( 2000 , p.4430) states, “Habitus is not destiny; but symbolic action cannot, on its own, without transformation of the conditions of the production and transformation of dispositions, extirpate bodily beliefs, which are passions and drives that remain totally indifferent to the injunctions or condemnations of humanistic universalism (itself, moreover, rooted in dispositions and beliefs)”, which emphasizes the difficulties in transforming people's engrained habits and implicit beliefs. Similar results of regressing back to “normal behaviors” were also observed in semester-long analytics visualization interventions for students (e.g., Zhou et al, 2021 ). As such, future research should seek to measure the effects of data-driven technologies on teaching behaviors over an extended period, to allow time for change to become integrated into teachers' habitus and sustained.…”
Section: Discussionsupporting
confidence: 70%
“…As Bourdieu ( 2000 , p.4430) states, “Habitus is not destiny; but symbolic action cannot, on its own, without transformation of the conditions of the production and transformation of dispositions, extirpate bodily beliefs, which are passions and drives that remain totally indifferent to the injunctions or condemnations of humanistic universalism (itself, moreover, rooted in dispositions and beliefs)”, which emphasizes the difficulties in transforming people's engrained habits and implicit beliefs. Similar results of regressing back to “normal behaviors” were also observed in semester-long analytics visualization interventions for students (e.g., Zhou et al, 2021 ). As such, future research should seek to measure the effects of data-driven technologies on teaching behaviors over an extended period, to allow time for change to become integrated into teachers' habitus and sustained.…”
Section: Discussionsupporting
confidence: 70%
“…As a result, "passengers" would be expected to report higher peer engagement. However, previous research reported that students may have misconceptions about others' engagement during collaboration without any help [52]. According to our result, some students who occupy too much speaking time in group discussions may not be aware of others' engagement in collaborative learning.…”
Section: Discussioncontrasting
confidence: 47%
“…Since driver students were actively discussing with each member of the group, they tended to think everyone was actively involved in collaboration. Therefore, as previous research suggested, providing information on individual student's engagement may help them to be aware of each other's contributions to collaborative learning [52]. In this study, neither the "drivers" nor the passengers were aware of others' engagement accurately, therefore needed external scaolding to regulate their own behaviours as well as others' behaviours.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations